Modern Social Economy as a Response to Unmet Social Needs of Polish People - Lewandowska-Bratek, Justyna (Studia Oeconomica Posnaniensia, 2015)
As a result of the cultural and historical background the contemporary Polish social economy is characterized by an underdeveloped non-profit sector, marginal mutualisation sector and a decreasing cooperative sector [Nałęcz 2008a]. The main goal of social economy operators is to complement the activities of two other sectors in solving social problems. Moreover, they take part in social integration, realize social unity programmes, equalize the opportunities to participate in various areas of social life , have an influence on changing the citizens' way of thinking, improve social order, develop competencies to fulfill social roles, especially when it comes to marginalized people. The social economy operators have great influence on social capital development, smooth the effects of great social changes and build relationship networks. The social economy also represents the new approach to local development. Currently in Poland strategic plans to revive the third sector and to stabilize the social economy of our country are being created.